Social Determinants of Health in India: Reimagining of Dr. B.R. Ambedkar’s Vision in the Light of Marginalized Communities - Kanhaiya Tripathi; Diksha Kanwat; Shankar Lal Bika; Jaspal Kaur; Neelu Rawat; Ashwani Kumar; Bhupinder Singh; Doggala Raju Kumar; Bawa Singh (Social Sciences)
The ongoing existence of health disparities in marginalized communities in India can be attributed to social health determinants such as poverty, caste, gender, and limited access to education and healthcare. Dr. B.R. Ambedkar, an iconic figure in Indian social reform and the driving force behind the Indian Constitution, acknowledged the significance of the social determinants of health influencing health outcomes. This paper explores Dr. Ambedkar’s vision of addressing health disparities, with a focus on his contributions to public health policy and the promotion of social justice. Additionally, it analyses the ongoing perpetuation of inequality through the examination of social determinants of health and explores how Ambedkar’s vision can provide guidance for present public health strategies. The analysis highlights the importance of strong primary healthcare systems, recognizing universal healthcare as an essential human right through the vision of Dr. Ambedkar. It also advocates for greater government funding and policy coordination to effectively tackle health disparities.